The Influence of Business Incubators on Entrepreneurial Economy in Makassar City, Makassar District East bara-baraya village - Zulkarnain, Muhammad Qadafi; Tawe, Amiruddin; Rakib, Muhammad; Sulolipu, Andi Annisa (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
In recent decades, entrepreneurship has become one of the main pillars of economic development, especially in developing countries such as Indonesia. Makassar City, as one of the economic centers in Eastern Indonesia, has an important role in encouraging the growth of the small and medium enterprise (SME) sector. One of the efforts made by the government and various institutions is to develop a Business Incubator Program, which aims to accelerate the growth of entrepreneurs through educational support, training, and guidance. In Makassar District, Bara-Baraya Timur Village, the development of local entrepreneurs is getting more attention. Business incubators in this area offer programs to help local entrepreneurs develop business skills, increase access to capital, and open wider networks. Although business incubators have proven successful in various countries, their implementation in each region can certainly provide different results, depending on the characteristics of the economic and social environment. In Bara-Baraya Timur Village, there are several challenges faced by one of the local entrepreneurs interviewed by the researcher, such as lack of management skills, and increasingly tight competition. Therefore, the researcher decided to conduct further research on “The influence of business incubators on the entrepreneurial economy in Makassar City, Bara-Baraya Timur Village”.